In situ laser irradiation: the kinetics of the changes in the nonlinear/linear optical parameters of As50Se40Sb10 thin films for photonic applications. Issue 26 (30th April 2021) - Sahoo, D.; Priyadarshini, P.; Dandela, R.; Alagarasan, D.; Ganesan, R.; Varadharajaperumal, S.; Naik, R.
Abstract : The photosensitivity of amorphous chalcogenide thin films brings out light-induced changes in the nonlinear and linear optical parameters upon sub-bandgap and bandgap laser irradiation. Abstract : The photosensitivity of amorphous chalcogenide thin films brings out light-induced changes in the nonlinear and linear optical parameters upon sub-bandgap and bandgap laser irradiation. The present work reports the in situ laser irradiated changes in the optical properties of As50 Se40 Sb10 thin films. The thermally evaporated film showed an exponential decrease in optical bandgap and increase in Urbach energy. The decay rate of the bandgap was 6.24 min and growth rate of Urbach energy was 6.67 min respectively. The dynamics of photo-induced changes were observed from the changes in linear refractive index and its dependent parameters such as 3 rd order nonlinear susceptibility, nonlinear refractive index, dispersion and dielectric parameters. The conversion of heteropolar to homopolar bonds induced the photodarkening mechanism that changed the dispersion parameters. The decrease in E d and E o reduced the oscillator strength along with the zero-frequency dielectric constant. The optical and electrical conductivity changed significantly with time. The changes were saturated with time which brings stability in the film properties that is useful for various optical applications. However, no structural and compositional changes upon laser irradiation were noticed from the X-ray diffraction and EDX studies respectively. The surface homogeneity was checked from the FESEM picture.